Derrubando cercas e dialogando saberes: desafios para uma extensão universitária transformadora em assentamentos rurais no sudeste da Amazônia Paraense - Silva, Leandro Ferreira da (Universidade Federal de São Carlos, 2022)
In line with the objectives and purposes for which they were created, it is in the genesis and in the attributions given to the Federal Institutes “to develop extension activities according to the principles and purposes of Vocational and Technological Education (EPT), in articulation with the world of labor and social segments, and with an emphasis on the production, development and dissemination of scientific and technological knowledge” (BRASIL, 2008). In this sense, by establishing the articulations of the EPT through academic and technological knowledge and the surrounding community, the University Extension is understood as spaces for the production of knowledge and the dialogue of systematized knowledge between the academic and the popular that result in the democratization of the knowledge. In this perspective, the starting hypothesis considers the fact that the IFPA - Campus Rural de Marabá (CRMB) is located within a settlement area and both are symbols of the achievements of the struggle and effective action of social and union movements in the countryside for the right to land. and the EPT, resulting in a public education institution based on the concept of rural education, agroecology and pedagogical alternation. Therefore, these characteristics changed the logic of making the University Extension, making it more transformative. In this research, the question is: Have university extension practices for agrarian reform settlers in the southeast of Pará Amazon in the EPT experiences in the IFPA-CRMB field have been marketing, assistentialist and/or transformative? In order to answer this question, the objective of this thesis is to understand the extensionist practices affirmed to the settlers in the EPT field experiences, taking as a case the IFPA-CRMB and the Agrarian Reform Settlements. For this, the research combines four distinct and interconnected studies. The first study describes the struggle for land and the constitution of rural settlements in southeastern Pará and the presence of the IFPA-CRMB within this territory; second, it seeks to discuss the conceptions and foundations of the EPT through the analysis of the work and education category, which give us support to discuss the ideas that were being established and the factors that influenced and legitimized the conceptions of the EPT in the face of the interests of the ruling class and the training the workforce in the stages of Brazilian capitalist development; The third seeks to base itself on legal and theoretical frameworks that deal with the concepts and conceptions of University Extension and its identity, as well as its constitution over time and its relationship with teaching and research and the place it occupies today in EPT ; and the fourth presents the University Extension at EPT at IFPA-CRMB through its projects, narratives and experiences. As part of this stage, a study was carried out of five extension projects carried out with the Agrarian Reform settlers with a focus on the dialogue of knowledge. For the scope of the research, the investigation took the perspective of historical-dialectical materialism, and used as a methodological route: bibliometrics, document analysis, semi-structured remote interview and virtual questionnaire. The results achieved allow us to conclude that the university extension carried out in the Settlements, despite the limitations found, can play a significant and transformative role in these territories in order to overcome inequalities. Studies show that university extension, when constituted from the constant interaction between the IFPA-CRMB, social movements, settlers and all democratic forces in society, can gain contours that transcend a welfare and/or marketing extensionist conception.
Breaking down fences and dialoguing knowledge: challenges for a transformative university extension in rural settlements in the southeast of Pará's Amazon
Keywords: Educação Profissional e Tecnológica; Política educacional; Institutos Federais; Extensão universitária; Assentamentos rurais; Amazônia Paraense; Professional Education; Educational politics; Federal Institutes; Extension; Rural settlements; Paraense Amazon; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO